Aspects of Bundo Kanduang Minangkabau Cultural Studies - Dermanto, Alin (Enigma Institute, 2023)
The study of the Bundo Kanduang Minangkabau culture demonstrates the crucial role that these elderly women or mothers play in the matrilineal society of West Sumatra, Indonesia. The role and meaning of Bundo Kanduang are very deep and cover various cultural, social, and spiritual aspects. Bundo Kanduang cultural studies help in understanding how strong the role of women is in Minangkabau culture and maintaining the uniqueness of this matrilineal society. They are protectors of cultural heritage, guardians of cultural values, and respected spiritual leaders. Through their roles and functions, the Bundo Kanduang maintain the continuity of the rich and valuable Minangkabau culture, playing a central role in maintaining harmony and wisdom in this society.